QUALITY OF LIFE AND PLASMA LEVELS OF MELATONIN AND STEROID HORMONES IN WOMEN WITH UTERINE LEIOMYOMA - Б. Соколов; А. Бербець; О. Юзько (Bukovynian State Medical University, 2024)
Uterine leiomyoma is the most common neoplasm of the female reproductive system, consisting of smooth muscle cells. This proliferative pathology accounts for up to 30 % of gynecological diseases, ranking second after pelvic infl ammatory processes. The appearance of clinical symptoms of uterine leiomyoma negatively aff ects the quality of life of such patients. It is also known that uterine leiomyoma is associated with changes in hormonal regulation in the female body; in particular, many researchers have noted an increase in blood levels of reproductive hormones, namely estradiol, in comparison with healthy women. However, the role of such an important hormone as melatonin, which has antioxidant properties and is capable of activating the processes of physiological apoptosis, in this disease is not fully understood. These processes require the most detailed study. The aim of the study was to estimate the quality of life and levels of melatonin and steroid hormones in women of reproductive age diagnosed with uterine leiomyoma. Materials and methods. 60 women of reproductive age diagnosed with uterine leiomyoma were studied. The control group consisted of 20 apparently healthy women of the same age. Quality of life was assessed using the UFS-QOL questionnaire. The level of melatonin in the women's blood was determined once, on an empty stomach, at 8 o'clock in the morning, using the Human MT (melatonin) ELISA kit; also, the blood plasma concentrations of reproductive steroid hormones (estradiol and progesterone) in the follicular phase (5th day of the menstrual cycle) were measured using the MAGLUMI diagnostic kits for immunochemoluminescence analysis. Statistical processing was performed using the MedCalc software package. The study was approved by the Commission on Biological and Medical Ethics of the Higher State Educational Institution of Ukraine «Bukovinian State Medical University» (Minutes № 4 of December 22, 2020) and was conducted in strict accordance with the Code of Ethics of the World Medical Association (Declaration of Helsinki) for experiments involving human subjects. All patients signed an appropriate informed consent. The publication is a fragment of the research work of the Department of Obstetrics and Gynecology of Bukovinian State Medical University «Preserving and restoring of the reproductive health of women and girls with obstetric and gynecological pathology». State registration number: 0121U110020. Period of conduction: 01.01.2021-12.2025. Results. It was found that patients of reproductive age with uterine leiomyoma have a probable decrease in overall self-assessment of quality of life (28.71 ± 14.65 points according to the UFS-QOL questionnaire, in the control group 98, 15 ± 3.45 points, p<0.01), sexual function (32.50 ± 16.63 points, control group 99.38 ± 2.80 points, p<0.01), and internal wellbeing (29.83 ± 17.76 points, control group 99.90 ± 0.45 points, p<0.001). We also found that the level of melatonin in the blood of women of reproductive age suff ering from uterine leiomyoma probably decreased by 27.6 % (111.08 ± 18.54 ng/ml, in the control group 153.50 ± 8.47 ng/ml ± 3.17 pg/ml). The severity of the symptoms of the disease depends on the level of estradiol in blood plasma, which is described by the linear regression equation. Conclusions. 1. Patients of reproductive age diagnosed with uterine leiomyoma have a signifi cant decrease in general self-assessment of quality of life, sexual function, and internal well-being compared to healthy women of the same age group. 2. The level of melatonin in the blood of women of reproductive age suff ering from uterine leiomyoma signifi cantly decreases (by 27.6 %), and the concentration of estradiol in such patients signifi cantly increases (by 2.97 times), compared to healthy women of the same age group. 3. In women of reproductive age suff ering from uterine leiomyoma, the severity of symptoms of the disease depends on the level of estradiol in blood plasma. This relationship is described by a linear regression equation that may have prognostic value in predicting the severity of disease symptoms.